2019
DOI: 10.1177/0361198119843262
|View full text |Cite
|
Sign up to set email alerts
|

Benefit-to-Cost Analysis Framework for Intersection Illumination: A Case Study of Rural Conventional Intersections in Georgia

Abstract: Lighting provides one of the most effective night-time intersection safety countermeasures. However, lighting is also one of the main contributors to intersection maintenance and operation costs. For a public transportation agency with jurisdiction over many intersections, the system-wide lighting costs can significantly deplete already limited funds for other important maintenance projects. A sound framework for conducting benefit-to-cost trade-off analysis would be beneficial to transportation agencies. Unfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…The properly calibrated model can then be used to run simulations of different alternative scenarios. These models have been used in the past to evaluate the effectiveness of specific maintenance measures involving, for example, pavements [30][31][32], lighting [33,34], left-turn maneuver signal [35], shoulder paving [36], medians [37], rumble strips [38], or generally cost-effective interventions [39]. However, the literature studies often deal with the evaluation of each intervention separately, without considering possible solutions affecting different infrastructure characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The properly calibrated model can then be used to run simulations of different alternative scenarios. These models have been used in the past to evaluate the effectiveness of specific maintenance measures involving, for example, pavements [30][31][32], lighting [33,34], left-turn maneuver signal [35], shoulder paving [36], medians [37], rumble strips [38], or generally cost-effective interventions [39]. However, the literature studies often deal with the evaluation of each intervention separately, without considering possible solutions affecting different infrastructure characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been also observed that increased intensity of road lighting decreases the number of accidents with pedestrian of 59%. Similarly, increased intensity of roadway lightning and installation of flashing warning signs acts with a reduction of pedestrian crashes of 57% in nighttime and a significant decrease in daytime, about 21%(Zgeer et al, (2006);Nassar et al, (2011);Scott et al, (2012);Bassani et al, (2012);Niaki et al, (2014);Bichicchi et al, (2017);Gibbons at al., (2015);Wei et al, (2016); Bullough et al, (2017 Bullough et al, ( ), (2021;Wang et al, (2018);Gbologah et al, (2019);Bhagavathula et al, (2019Bhagavathula et al, ( ), (2020;Costa et al, (2017), (…”
mentioning
confidence: 99%